Acción y sentido en John Dewey - Ballesteros, Juan Carlos Pablo (Sapientia, 2006)
Accoridng to Dewey, human action is explained in the relation between means and consequences. He starts by establishing his conception of knowledge and the function of intelligence. In so far as there are no unchanging and eternal essences, knowledge does not consists in adapting to such realities. The influence of James's psychology was important for his epistemological conception, and in his early works, the explanation of ^ human action based on habits and the social environment is already present. His instrumentalism holds that our ideas depend on actions and that moral judgments are objective because all practical judgments are objective. This papen seeks to determine if Dewey can justify such objectivity.